2014
DOI: 10.1111/glob.12044
|View full text |Cite
|
Sign up to set email alerts
|

Transnational networks and transcultural belonging: a study of the Spanish second generation in Switzerland

Abstract: Migration scholars often assume a close association between transnational social practices and transcultural forms of belonging. Nonetheless, we argue that the distinction of both concepts is analytically important and helpful in understanding the transnational lives of second‐generation migrants. To analyse the biographical accounts and network maps of second‐generation Spaniards living in Switzerland, we draw a theoretical distinction between social practice (transnational networks) and forms of belonging (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 31 publications
0
17
0
2
Order By: Relevance
“…This allowed us to differentiate what Levitt and Glick Schiller (2004) had termed transnationalism as ways of being and ways of belonging. The analysis of the interplays between networks and forms of belonging across borders suggested that transnational networks and transcultural belonging do not simply go hand in hand (Richter and Nollert 2014). The typology presented earlier was therefore adapted and differentiated to comprise the following types: (1) continuity of transnational networks and transcultural belonging-networks, as well as feelings of belonging, were continuously maintained since childhood; (2) reconnection of transnational networks and revitalization of transcultural belonging-this type revitalized the transcultural feeling of belonging after also reconnecting the transnational networks; (3) belonging without transnational ties-for this type (in the earlier typology represented by the "Spain of one's own") the feeling of belonging is not linked to transnational networks, in particular not to the networks inherited from the parents.…”
Section: Major Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This allowed us to differentiate what Levitt and Glick Schiller (2004) had termed transnationalism as ways of being and ways of belonging. The analysis of the interplays between networks and forms of belonging across borders suggested that transnational networks and transcultural belonging do not simply go hand in hand (Richter and Nollert 2014). The typology presented earlier was therefore adapted and differentiated to comprise the following types: (1) continuity of transnational networks and transcultural belonging-networks, as well as feelings of belonging, were continuously maintained since childhood; (2) reconnection of transnational networks and revitalization of transcultural belonging-this type revitalized the transcultural feeling of belonging after also reconnecting the transnational networks; (3) belonging without transnational ties-for this type (in the earlier typology represented by the "Spain of one's own") the feeling of belonging is not linked to transnational networks, in particular not to the networks inherited from the parents.…”
Section: Major Resultsmentioning
confidence: 99%
“…3 The research design and the data collection were developed by Marina Richter. Michael Nollert as the co-author was involved in data analysis and interpretation of the results (see also Richter and Nollert 2014). second-generation transnationalism and allowed the selection of specific cases for further research. We opted for such a narrowing of the sample because it was an easy task to find people of the second generation, but it was difficult to select people according to their transnational lives beforehand, as this is a rather abstract notion and difficult to explain.…”
Section: The Research Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, interviewees over the age of about 60 continued to construct their 'transnational ways of belonging' around a collective 'Bihari' identity, an identity that was the product of a unique history and shared experience. As this case demonstrates, a sense of transcultural belonging (to Bihar or to a shared 'Bihari' identity) can continue even when transnational networks (with India in this case) have ceased to function (Richter and Nollert 2014). Interviewees who experienced the Liberation War when they were old enough to have a sense of themselves as considered 'Bihari' by others, and the sense of a 'Bihari' community of which they were a part, have carried that with them.…”
Section: 'Diasporic Consciousness'mentioning
confidence: 85%
“…The literature on transnational migration became replete with what are fundamentally spatial terms including "transnational social space" (Faist 1998), "transnational community" (Levitt 2001;Vertovec 1999) and "transnational social formation" (Guarnizo 1997). Scholars offered a "growing body of empirical studies on various aspects of transnational social spaces" (Richter 2012).…”
Section: Subsequent Transnational Migration Scholarship: Time and Spamentioning
confidence: 99%